Protection of Rafflesia through the appreciation of the Dusun’s indigenous knowledge; A preliminary case study at Poring-Sabah - Robert Francis Peters; Yap, Yih Ting (Penerbit UMS, 2016)
Rafflesia is a rare parasitic plant species that is becoming vulnerable to extinction due to the loss of its habitat. To protect this plant from extinction, stakeholders need to coordinate their efforts in maintaining its habitat. Indigenous people are a stakeholder and appreciating their indigenous knowledge about plant and habitat management could help protect the plant. To investigate the potential effects of appreciating indigenous knowledge about Rafflesia, a case study was carried out. The investigation was carried out at Poring-Sabah with 59 Dusun residents and tourists interviewed using questionnaires. A content analysis was carried out on the questionnaires. The investigation uncovered the existence of indigenous names and uses for Rafflesia. Apart from the plant being used as a tourist attraction, the analysis showed that there are some traditional health uses for the Rafflesia plant. The investigation also noted a higher awareness about the protection of the Rafflesia plant among the Dusun community compared to the tourists. A description about the protection of the Rafflesia plant through the integration of the Dusuns’ indigenous knowledge with current knowledge and management systems is provided.